The prevalence of corneal guttata and its related risk factors in a Thai population: a community-based study in central Thailand - Vilavun Puangsricharern; Vannarut Satitpitakul; Susama Chokesuwattanaskul; Thanapoom Rattananupong; Thanachaporn Kittipibul; Phattrawan Pisuchpen; Keeratika Sangsao; Usanee Reinprayoon; Ngamjit Kasetsuwan (Scientific Reports)
Abstract This is a large cross-sectional, population-based survey to investigate the prevalence of central corneal guttata in the Thai population. Two communities in the central region of Thailand are (1) Phanat Nikhom district, Chonburi, and (2) Khlong Toey district, Bangkok. All participants completed an interview and ophthalmic examination. Overall, 990 participants aged ≥ 40 years were included. The prevalence of central corneal guttata was 40.80% (399/978 participants); 328/978 participants (33.54%) exhibited modified Krachmer grade I corneal guttata. The study utilized definitive diagnosis and severity grading, using the modified Krachmer grading scale, to estimate the prevalence within the general population and to identify potential risk factors. The presence of central corneal guttata was evaluated by three corneal specialists (VP, VS, and PP) using a slit-lamp biomicroscope and the NIDEK CEM-530 specular microscope (NIDEK, Aichi, Japan). The estimated overall prevalence in the Thai population was 45.76%, with an approximate female-to-male ratio of 1.35:1. Multiple logistic regression analysis showed that only age ≥ 50 years, compared with age 40–49 years, was a significant risk factor for the presence of central corneal guttata. In conclusion, this study showed that the prevalence of central corneal guttata (mainly sporadic cases) in the Thai population was as high as 45.76%.